Engineering nitrilases for enhanced thermostability - Dlamini, Lenye Sebenzile (Department of Integrative Biomedical Sciences (IBMS), 2025)
Cyanide dihydratase from Bacillus pumilus C1 (CynDpum) catalyses the hydrolysis of cyanide to formic acid and ammonia. CynDpum has the potential to remediate cyanide-containing wastewater. However, two obstacles hinder the commercial use of recombinantly expressed CynDpum as a biocatalyst: reduced activity at pH>8 which is typical of cyanide-rich environments, and inactivation at temperatures above 42 °C. Several variants with either enhanced thermostability or activity at alkaline pH have been discovered by random mutagenesis and directed evolution; however, these methods are slow and limited in their explorable sequence space. The aim of this project is to investigate the structural and chemical determinants of thermostability in cyanide dihydratases. This was achieved through rational site-saturation mutagenesis, followed by experimental validation using nanoscale differential fluorimetry, negative stain and cryogenic electron microscopy, and single-particle analysis. In this study, atomic resolution structures of wild-type CynDpum and its variant CynDpum (Q86R/H305K/H308K/H323K) were employed to predict, using empirical force fields, the change in Gibb's free energy resulting from mutating each amino acid in the atomic resolution structure of the variant (amino acids 3-319) to each of the remaining 19 residues. Favourable Gibb's free energy changes were used as indicators of the thermostability of CynDpum variants and validated experimentally using chemical denaturation monitored by nanoscale differential scanning fluorimetry. The thermodynamic favourability of six variants (S29A, T217I, T260I, Q86M, N119R, and E155R) was successfully validated. Negative stain electron microscope micrographs of these variants revealed that these variants formed helical fibres with increased length relative to wild-type CynDpum, indicating a positive correlation between a favourable change in Gibb's free energy of protein unfolding and fibre length. The observed favourable Gibb's free energy change of the surface variants (S29A, T217I, and T260I) is attributed to the reduced number of solvent-accessible amino acid sidechains, promoting protein folding and oligomerisation. Variants N119R and E155R, located along the groove of the helical assembly, form electrostatic interactions across the grooves, thereby enhancing the structural rigidity of the quaternary structure and leading to a favourable Gibb's free energy change. These interactions were visualised in the 2.78 Å resolution atomic model of the E155R variant of CynDpum and the 3.26 Å resolution structure of CynDstu solved by cryo-electron microscopy. Analyses of the conventional interfaces (named A-, C-, D-, and E-) through which the CynDpum helix and cyanide dihydratase from Pseudomonas stutzeri AK61 (CynDstu) spiral are formed, revealed that the helical and spiral assemblies are predominantly stabilised through hydrophobic and electrostatic interactions occurring at the A and C interfaces, respectively. Additionally, examination of the C-terminal tail regions of the atomic-resolution structures of wild-type CynDpum, its variants (Q86R/H305K/ H308K/H323K, and E155R), and CynDstu revealed that the C-terminal tail stabilises all interfacial regions through specific interactions, demonstrating its critical structural and functional role in assembly formation and thermostability.